High prevalence of early onset mental disorders among long-term disability claimants. Issue 6 (12th March 2016) - Cornelius, L. R.; van der Klink, J. J. L.; de Boer, M. R.; Brouwer, S.; Groothoff, J. W.
Abstract: Purpose : To provide information on prevalence, comorbidity, age-of-onset and severity of mental disorders among persons claiming disability after long-term sickness absence. Method : Cross-sectional analysis of a cohort of Dutch disability claimants ( n = 346). Composite International Diagnostic Interview (CIDI) 3.0 was used to generate DSM-IV classifications of mental disorder, age-of-onset and severity; registry data were used on demographics and ICD-10 classifications of somatic disorder. Results : The mean age of respondents was 49.8 (range 22–64). The most prevalent broad categories of mental disorders were mood and anxiety disorder with a 12-month prevalence of 28.6% and 32.9%, respectively. Mood and most anxiety disorders had ages of onset in adolescence and early adulthood. The phobias start at school age. Of all respondents, 33.7% had ≥1 12-month mental disorder. Co-occurrence of substance use disorders, phobias and depression/anxiety disorders is frequent. Urogenital and gastrointestinal diseases, and cancer coincide with 12-month mental disorder in 66.7%, 53.9% and 51.7% of cases, respectively. More than two out of three specific mental disorders are serious in terms of disability and days out of working role. Conclusions : Disability claimants constitute a vulnerable population with a high prevalence of serious mental disorder, substantial comorbidity and ages-of-onset in early working careers. More research is needed to help prevent long-term sickness absence and disability of claimants with mental health problems. Implications for Rehabilitation: This study shows common mental disorders, such as mood and anxiety disorders, to be highly prevalent among persons claiming disability benefit after long-term sickness absence, to have early onsets and to often co-occur with somatic disorders. Professionals in primary and occupational health care should assess need for treatment of workers at risk, while at the same time being careful not to medicalize normal life problems. Insurance physicians assessing disability benefit claims should identify factors that caused claimants to call in sick and start interventions to promote return to work.